How would monetary policy matter in the proposed African monetary unions? Evidence from output and prices - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
We analyze the effects of monetary policy on economic activity in the proposed African monetary unions. Findings broadly show that: (1) but for financial efficiency in the EAMZ, monetary policy variables affect output neither in the short-run nor in the long-term and; (2) with the exception of financial size that impacts inflation in the EAMZ in the short-term, monetary policy variables generally have no effect on prices in the short-run. The WAMZ may not use policy instruments to offset adverse shocks to output by pursuing either an expansionary or a contractionary policy, while the EAMZ can do with the 'financial allocation efficiency' instrument. Policy implications are discussed.
Keywords: E51; E52; E58; E59; O55; 330; Monetary Policy; Banking; Inflation; Output effects; Africa